MTP genetic variants associated with non-alcoholic fatty liver in metabolic syndrome patients - Weaam Gouda; Esmat Ashour; Yehia Shaker; Wafaa Ezzat (Genes and Diseases, 2017)
This study was performed for investigation the relationship between variants of MTP gene polymorphism and the development of NAFLD in patients with and without MS. The study was included 174 NAFLD patients (106 with MS and 68 without MS), and 141 healthy control subjects. The 493 G/T polymorphism of MTP gene was evaluated by PCR-RFLP method. The frequency of MTP TT genotype and T allele were significantly higher in NAFLD patients when compared to healthy controls. Moreover, a significant association in MTP gene polymorphism was observed in NAFLD patients with MS compared to NAFLD patients without MS and controls. Our study suggested that MTP 493 G/T gene polymorphism may act as susceptibility biomarker for NAFLD and MS.